Integrated Approach for Liming and Fertilizer Application on Yield of Cabbage and Cauliflower in Acidic Soil of Sylhet (Bangladesh Agronomy Journal, 2016)
An experiment was conducted at farming system research and development (FSRD) site, Jalalpur and multi location testing (MLT) sites, Moulvibazar and Zokigonj during 2013-2015 to study the effect of liming and fertilizers levels on the yield of cabbage and cauliflower in acidic soil of Sylhet. Trials were laid out in a factorial randomized block design with six dispersed replications. The treatments of fertilizer managements were M1: soil test based (STB) recommended fertilizer and M2: fertilizer dose practiced by the farmers (FP) and the level of limes were L1:0 t ha-1; L2: 1 t ha-1 and L3: 2 t ha-1. Results revealed that yields of cabbage and cauliflower responded significantly to fertilizer doses, levels of lime, and their combinations in all the locations. Soil test based fertilizer rate (M1-N201, P63, K65, S23, Zn0.5 for cabbage and M1-N157, P57, K116, S20, Zn0.5 Kg ha-1 for cauliflower) gave the maximum head and curd yields of cabbage and cauliflower, respectively. The levels of lime at the rate 2 t ha-1 (L3) provided the highest yields of cabbage and cauliflower in all locations. Dolomite lime @ 2 t ha-1 in combination with recommended fertilizer (M1L3) gave the highest yields and maximum economic returns of cabbage and cauliflower in all locations. However, it was identical with 1 t ha-1 of dolomite lime of similar dose of fertilizer nutrients. Therefore, application of lime at the rate 1 t ha-1 with STB recommended fertilizer management (M1) could be enough for profitable economic returns for cultivating cabbage and cauliflower in strongly acidic soil in Sylhet.Bangladesh Agron. J. 2016, 19(1): 49-57